INTEGRATION OF VIRTUAL REALITY IN FOREIGN LANGUAGE TEACHING: ENHANCING EFFECTIVENESS AND STUDENT ENGAGEMENT - Latifatul Isro'iyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The integration of Virtual Reality (VR) technology into foreign language teaching has emerged as a transformative approach to enhance both the effectiveness and engagement of students. This study explores the impact of VR on language acquisition by examining its ability to provide immersive and interactive learning environments that traditional classroom settings may lack. A mixed-methods research design was employed, combining quantitative measures of language proficiency with qualitative assessments of student engagement and motivation. The study involved 200 participants from various educational institutions, utilizing VR applications specifically designed for language learning. Results indicate a significant improvement in language proficiency scores among students who engaged with VR-based instruction compared to those who received conventional teaching methods. Additionally, qualitative data revealed heightened levels of motivation, engagement, and positive attitudes toward language learning within the VR group. The findings suggest that VR can facilitate experiential learning, contextual understanding, and real-time feedback, thereby addressing common challenges in language education such as lack of practice opportunities and limited exposure to native speakers. The study also discusses the implications for curriculum design, teacher training, and the scalability of VR technologies in diverse educational settings. While acknowledging potential barriers such as cost and accessibility, the research underscores the potential of VR to revolutionize foreign language education by creating dynamic, learner-centered environments that foster deeper cognitive and affective engagement. Future research directions include longitudinal studies to assess long-term language retention and the exploration of VR's role in developing advanced language skills such as pronunciation and conversational fluency.